Social group formation and genetic relatedness in reintroduced Asian elephants (Elephas maximus) in Thailand - Chatchote Thitaram (2018)
© 2015 Elsevier B.V. Captive-held elephants were recruited from several parts of Thailand and released as part of a reintroduction project. Wild elephants with a herd matriarch generally contain the same matrilineal line and are genetically related. However, reintroduced elephants are less likely to be related, but are known to establish social groups. The objective of this study was to investigate the genetic relatedness and behavioral relationships of elephants reintroduced into forested areas in central and northern Thailand. Blood samples were collected from 53 elephants before release into the Sublanka (SLK) and Doi Phamuang (DPM) Wildlife Sanctuaries, and DNA was extracted for microsatellite and mitochondrial analysis. Direct observations of social bonding behaviors were done weekly for 12 months after release, and an association index (AI) calculated for each individual. The results showed a low relatedness for both populations; the observed heterozygosity and number of mitochondrial haplotypes were 0.739 and 13 at SLK (n = 26), and 0.808 and 11 at DPM (n = 27), respectively. Across both locations, 33 elephants formed into 11 groups (range 2-6 individuals/group). The average AI and pairwise genetic relatedness of elephant groups were 0.517 ± 0.039 and 0.078 ± 0.019, respectively, and were not correlated (r = -0.036; p= 0.78). Twenty elephants were not associated with specific groups and had average AI and pairwise genetic relatedness of 0.002 ± 0.001 and 0.047 ± 0.013, respectively, which were not correlated (r= -0.074; p= 0.491). Several mitochondrial haplotypes were found within the same group. Thus, social bonding of the reintroduced elephants was not influenced by genetic relatedness. Rather, groups formed in association with the presence of an elephant calf. Additionally, many elephants occasionally preferred isolation. Thus, reintroduction procedures should favor introducing elephant calves, or adults with calves to increase the chance of group formation and establishment of stable elephant herds.